2013
DOI: 10.1093/icesjms/fst020
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting life history characteristics of the eightbar grouper Hyporthodus octofasciatus (Pisces: Epinephelidae) over a large latitudinal range reveals spawning omission at higher latitudes

Abstract: Wakefield, C. B., Newman, S. J., Marriott, R. J., Boddington, D. K., and Fairclough, D. V. 2013. Contrasting life history characteristics of the eightbar grouper, Hyporthodus octofasciatus (Pisces: Epinephelidae), over a large latitudinal range reveals spawning omission at higher latitudes. – ICES Journal of Marine Science, 70: 485–497. Demographic data on deep-water groupers are limited despite them being highly exploited throughout the Indo-Pacific. In Western Australia, the continuous distribution of the ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 34 publications
5
50
0
Order By: Relevance
“…This ageing precision error was also within previous estimates for long-lived deepwater teleosts from the same continental slope locations in southwestern Australia, i.e. 1.95 and 4.89% (Wakefield et al 2010(Wakefield et al , 2013). All age-based studies of P. americanus and the congeneric P. oxygeneios have found that a single opaque and successive translucent zone is de posited annually in their sagittal otoliths, and that counts of these alternating growth zones can be used to derive age estimates (i.e.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This ageing precision error was also within previous estimates for long-lived deepwater teleosts from the same continental slope locations in southwestern Australia, i.e. 1.95 and 4.89% (Wakefield et al 2010(Wakefield et al , 2013). All age-based studies of P. americanus and the congeneric P. oxygeneios have found that a single opaque and successive translucent zone is de posited annually in their sagittal otoliths, and that counts of these alternating growth zones can be used to derive age estimates (i.e.…”
supporting
confidence: 90%
“…Sample sizes of P. americanus were only available in small numbers when compared to those of other teleosts that were sampled from the same commercial and recreational catches (e.g. Wakefield et al 2010Wakefield et al , 2013. It is uncertain whether this lower relative abundance in catches reflects the natural abundance of this species on the continental slope off southwestern Australia, or that higher abundances of this species occur at greater depths than were fished during the period of collection for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, temperature is likely contributing to the observed latitudinal variation in growth of E. carbunculus in the Pacific Ocean. A similar trend was not observed in the Indian Ocean due to a lack of samples from latitudes >20 • S. This might at least partially explain the observed differences in growth between oceans, as fish >50 cm FL in the Pacific Ocean were only sampled from latitudes >20 • S. Wakefield et al (2013b) observed a similar latitudinal pattern in the Indian Ocean for the deepwater grouper Hyporthodus octofasciatus, with a significantly larger length-atage at higher latitudes. Analyses of growth for E. carbunculus from 1) latitudes south of 20 • S in the Indian Ocean, and 2) its latitudinal distribution in the northern Pacific Ocean, would clarify whether the relationship between growth and latitude are consistent with those observed in the south Pacific Ocean.…”
Section: Latitudinal Functionssupporting
confidence: 52%
“…The metapopulation paradigm may similarly apply to tropical deepwater species which have a strong association with benthic habitats that have a discontinuous and patchy distribution across ocean basins. However, studies of spatial variation in biological characteristics within a stock for tropical deepwater fishes are limited (Wakefield et al, 2013b. Therefore, it remains unclear whether the patterns of spatial variation in biological characteristics observed for many tropical shallow-water species are also prevalent in stocks of tropical deepwater species.…”
Section: Introductionmentioning
confidence: 99%
“…What has emerged is increasing evidence that many exploited reef fish species have life history strategies of extended life spans, slow growth, and, in the absence of fishing, an accumulation of older individuals-strategies usually associated with species in temperate (10-25°C) and deep (>30 m) waters (Choat and Robertson, 2002;Pears et al, 2006;Wakefield et al, 2013Wakefield et al, , 2015. Stocks that have such traits present challenges for fisheries managers, especially in developing countries where life history information is rarely collected (Polunin et al, 1996), mostly because of a lack of funding.…”
mentioning
confidence: 99%